As políticas de governo no Rio Grande do Sul de 2015 a 2018 e as condições de trabalho pedagógico na rede pública estadual: movimentos de continuidade do discurso sob a lógica do capital segundo posicionamentos do CPERS/Sindicato - Dressler, Marlize (2022)
This study is linked to the Research Line 2 – Public Educational Policies, Educative Practices, and their Interfaces from the Graduation Program in Education of Universidade Federal de Santa Maria – and to Kairós – Study and Research Group on Work, Public Policies, and Education. Its proposition arose after the verification of continuous discourses of government policies under the capital logic. The general objective of the paper was established based on this perspective: to analyze the policies of Rio Grande do Sul State Government, from 2015 to 2018, which were implemented after the State rearrangement, and their impact on the pedagogical working conditions of teachers from the state public educational system, in parallel with the positions made by the Center of Teachers from Rio Grande do Sul State (CPERS/UNION). The process of data analysis and production was carried out following the theoretical and methodological foundation of the Motion Analysis (MA), which consists of Kairós’ dialectic perspective on education study and research. Then, the discourses made by the State government, the State apparatus’ institution – the Federal Court of Accounts from Rio Grande do Sul (TCE-RS) –, and the CPERS/UNION were analyzed through the MA. We used as references the public documents available in the websites of the State government, of the public body, and of the institution that represents Education workers, which had been published in Sineta newspaper (both online and printed versions), from 2015 to 2018, to compare the subjects’ discourses. The analyzed discourses referred, mainly, to educational issues, especially regarding the pedagogical working conditions of teachers from the state public educational system based on the government policies applied back then. Thus, the meanings of these discourses were analyzed through charts, tables, diagrams, and figures, according to the bibliographic research. The basic references were based on the following analysis categories: totality, contradiction, and historicity. We have found the prominence of discourses related to the continuity of government policies in agreement with the capital logic, in which the ideological conception of an autonomous and sovereign State is subsumed to how the state policy forms the continuous reproduction of value, according to capital determinations. Therefore, we defend the thesis that the rearrangement in Rio Grande do Sul state, from 2015 to 2018, meant the continuity of the capital discourse motion. Thus, we highlight that the CPERS/UNION must extend the debate and criticism to beyond government policies, since the representative democracy process is limiting.